Exploring Geographic Influences on the Engagement Divide Between Male and Female Employees - Westover, Jonathan H.; Andrade, Maureen Snow (Journal of Management Policy and Practice, 2024)
This study analyzes survey data from over 500 U.S. employees to investigate how key workplace determinants uniquely relate to engagement for men and women within and outside of Utah. The aim is to address gaps in research examining potential gender variations and geographic influences on the drivers of discretionary effort at work. Traditional predictors like fulfillment of basic needs, individual contributions, teamwork, and growth were examined alongside the emerging construct of “worker activation,” reflecting empowering organizational cultures that motivate extra effort. Analyses included descriptive tests, gender-specific regression models, and assessments of activation variable impacts between genders, with findings revealing modest yet significant male-female disparities in average engagement levels. The multi-dimensional nature of engagement determinants also varied across genders and geographies. Activation was also found to significantly predict engagement across genders, validating its cross-cutting importance in conceptualization and offering implications for optimally designing inclusive strategies to inspire discretionary commitment and employee engagement both within and outside of Utah.